Advancements in understanding cardiotoxicity of EGFR- TKIs in non-small cell lung cancer treatment and beyond - Li, Xin; Lin, Yongping; Lin, Song; Huang, Jiayi; Ruan, Zhongbao (Frontiers in Pharmacology, 2024)
Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors (EGFR-TKIs) are a class of oral targeted anticancer drugs that have been demonstrated to significantly inhibit tumor progression and improve clinical prognosis in patients diagnosed with EGFRmutated tumors, particularly in those with non-small cell lung cancer. However, the sustained usage of EGFR-TKIs may cause potential cardiotoxicity, thus limiting their applicability. The primary objective of this review is to systematically analyze the evolving landscape of research pertaining to EGFR-TKI-induced cardiotoxicity and elucidate its underlying mechanisms, such as PI3K signaling pathway inhibition, ion channel blockade, oxidative stress, inflammatory responses, and apoptosis. Additionally, the review includes an exploration of risk assessment for cardiotoxicity induced by EGFR-TKIs, along with management and response strategies. Prospective research directions are outlined, emphasizing the need for more accurate predictors of cardiotoxicity and the development of innovative intervention strategies. In summation, this review consolidates recent research advances, illuminates the risks associated with EGFR-TKI-induced cardiac toxicity and presents crucial insights for refining clinical dosage protocols, optimizing patient management strategies, and unraveling the intricate mechanisms governing EGFR-TKI-induced cardiotoxicity.